Meroterpenoids with diverse structures and anti-inflammatory activities from Rhododendron anthopogonoides. (December 2020) - Shi, Qing; Li, Teng-Teng; Wu, Yong-Mei; Sun, Xin-Yu; Lei, Chun; Li, Jing-Ya; Hou, Ai-Jun
Abstract: Eight pairs of meroterpenoid enantiomers and four achiral meroterpenoids were isolated from Rhododendron anthopogonoides Maxim. Seventeen of them, named (+)-/(−)-anthoponoids A−G, (+)-daurichromene D, and anthoponoids H and I, are undescribed compounds with structural diversity. Their structures were characterized herein by a combined application of spectroscopic techniques, X-ray crystallographic analysis, ECD calculation, and the modified Mosher's method. (+)-/(−)-Anthoponoid A and anthoponoid I are the first Rhododendron meroterpenoids found to possess a hexahydroxanthene motif and a diterpene unit, respectively. Some isolates were identified as NF- κ B pathway inhibitors, and (+) - anthoponoid E, (−)-anthoponoid G, and anthoponoid H showed suppressive effects on LPS-induced inflammatory responses in RAW 264.7 macrophages. Graphical abstract: Eight pairs of meroterpenoid enantiomers and four achiral meroterpenoids were isolated from Rhododendron anthopogonoides, including seventeen undescribed compounds with structural diversity. Some of the meroterpenoids showed significant anti-inflammatory activities. Image 1 Highlights: Twenty meroterpenoids were isolated from Rhododendron anthopogonoides. Eight pairs of meroterpenoid enantiomers were resolved by chiral-phase HPLC . Seventeen meroterpenoids with structural diversity are undescribed. Some of the meroterpenoids showed significant anti-inflammatory activities.